Effects of anti‐IL5 biological treatments on blood IgE levels in severe asthmatic patients: A real‐life multicentre study (BIONIGE). Issue 4 (7th April 2022) - Contoli, Marco; Santus, Pierachille; Menzella, Francesco; Rocchi, Cindy; Radovanovic, Dejan; Baraldi, Federico; Martelli, Chiara; Casanova, Serena; Barbetta, Carlo; Micheletto, Claudio; Scichilone, Nicola; Beghè, Bianca; et al.
Abstract: Background: Mepolizumab and benralizumab are clinically effective biological treatments for severe eosinophilic asthmatic patients by hampering eosinophilic inflammation. The effects of these compound on the immunoglobulin (Ig)E T2 component are virtually unknown. Objectives: To evaluate the change in total IgE levels at 4 ± 2 months after initiation of the mepolizumab (primary outcome) or benralizumab. When available, the changes of blood inflammatory cell counts, lung function and asthma control test (ACT) were also assessed and correlated with changes in total IgE levels. Methods: Observational, retrospective, multicentre, cohort study. Severe eosinophilic atopic asthmatic patients treated with mepolizumab or benralizumab were included in the analysis. Results: Three‐month treatment (on average) with mepolizumab ( n = 104) or benralizumab ( n = 82) resulted in significantly higher reduction of blood eosinophil and basophil levels in patients treated with benralizumab compared to mepolizumab. Mepolizumab did not significantly modified the levels of blood total IgE during the study period, whereas benralizumab significantly reduced (−35%, p < 0.001) total blood IgE levels. In patients treated with benralizumab the reduction of blood total Ig‐E levels correlated with the reduction of blood basophils (but not eosinophils) and weakly with the improvement of asthma control. Conclusion: Benralizumab but not mepolizumab, treatment led to a significant reduction of circulating IgE level. The study provides different and specific mechanisms of action for anti‐IL5‐pathway treatments.